On the importance of diffusion and compound-specific mixing for groundwater transport: An investigation from pore to field scale - Rolle, Massimo; Chiogna, Gabriele; Hochstetler, David L.; Kitanidis, Peter K. (Journal of Contaminant Hydrology, 2013)
Mixing processes significantly affect and limit contaminant transport and transformation rates in the subsurface. The correct quantification of mixing in groundwater systems must account for diffusion, local-scale dispersion and the flow variability in heterogeneous flow fields (e.g., flow-focusing in high-conductivity and de-focusing in low-conductivity zones). Recent results of multitracer laboratory experiments revealed the significant effect of compound-specific diffusive properties on the physical displacement of dissolved species across a representative range of groundwater flow velocities. The goal of this study is to investigate the role of diffusion and compound-specific mixing for solute transport across a range of scales including: (i) pore-scale ( 10- 2 m), (ii) laboratory bench-scale ( 100 m) and (iii) field-scale ( 102 m). We investigate both conservative and mixing-controlled reactive transport using pore-scale modeling, flow-through laboratory experiments and simulations, and field-scale numerical modeling of complex heterogeneous hydraulic conductivity fields with statistical properties similar to the ones reported for the extensively investigated Borden aquifer (Ontario, Canada) and Columbus aquifer (Mississippi, USA, also known as MADE site). We consider different steady-state and transient transport scenarios. For the conservative cases we use as a metric of mixing the exponential of the Shannon entropy to quantify solute dilution either in a given volume (dilution index) or in a given solute flux (flux-related dilution index). The decrease in the mass and the mass-flux of the contaminant plumes is evaluated to quantify reactive mixing. The results show that diffusive processes, occurring at the small-scale of a pore channel, strongly affect conservative and reactive solute transport at larger macroscopic scales. The outcomes of our study illustrate the need to consider and properly account for compound-specific diffusion and mixing limitations in order to accurately describe and predict conservative and reactive transport in porous media. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Diffusion; Dilution index; Groundwater transport; Mixing; Numerical modeling